Answer:
![Area = 968000cm^2](https://tex.z-dn.net/?f=Area%20%3D%20968000cm%5E2)
Step-by-step explanation:
To be able to answer this question properly. I'll assume the length of the room is in meters.
So for the room, we have:
![Length = 12.8m](https://tex.z-dn.net/?f=Length%20%3D%2012.8m)
![Breadth = 850cm](https://tex.z-dn.net/?f=Breadth%20%3D%20850cm)
For the bed, we have:
![Length = 300cm](https://tex.z-dn.net/?f=Length%20%3D%20300cm)
![Breadth = 400cm](https://tex.z-dn.net/?f=Breadth%20%3D%20400cm)
First, we calculate the surface area of the room.
![A_1 = 12.8m * 850cm](https://tex.z-dn.net/?f=A_1%20%3D%2012.8m%20%2A%20850cm)
Convert all units to cm
![A_1= 12.8*100cm * 850cm](https://tex.z-dn.net/?f=A_1%3D%2012.8%2A100cm%20%2A%20850cm)
![A_1= 1 088 000 cm^2](https://tex.z-dn.net/?f=A_1%3D%201%20088%20000%20cm%5E2)
Next, we calculate the area of the bed
![A_2 = 300cm * 400cm](https://tex.z-dn.net/?f=A_2%20%3D%20300cm%20%2A%20400cm)
![A_2 = 120000cm^2](https://tex.z-dn.net/?f=A_2%20%3D%20120000cm%5E2)
The area of the space left is the difference between A1 and A2
![Area = A_1 - A_2](https://tex.z-dn.net/?f=Area%20%3D%20A_1%20-%20A_2)
![Area = 1088000cm^2 - 120000cm^2](https://tex.z-dn.net/?f=Area%20%3D%201088000cm%5E2%20-%20120000cm%5E2)
![Area = 968000cm^2](https://tex.z-dn.net/?f=Area%20%3D%20968000cm%5E2)
<span>You are given a rectangular picture measuring 8 inches by 7 inches. Also, Alistair wants this to be framed and that the total area is 34 square inches. The width of the frame is x inches. To solve the dimension of the frame with value of x we have:
We have to assume that x here will be equal to all sides of the frame and so, using the area of the rectangle, we can model the equation like this:
A = LW (where A is the area, L is the length and W is the width)
36 = (8 - x)(7 - x)
36 = 56 - 8x - 7x + x</span>²
<span>x</span>² - 15x +20 = 0 → model of our equation and in quadratic form
x² - 15x + 20 = 0
using a calculator, x = 1.48 inches
<span>
3.Use the equation you created in part A to find the width of the picture frame</span>
Step-by-step explanation:
these are the answers of your questions
Answer:
the 2nd option f(-4) = g(-4) and f(0) = g(0)
Step-by-step explanation:
the right answer was the same x and sampe y. it means in their intersection for both f(x) anad g(x)
so the correct answer is f(0) = g(0) and f(-4) = g(-4)
Answer:
$600
Step-by-step explanation: